IDH1/2 mutations in acute myeloid leukemia patients and risk of coronary artery disease and cardiac dysfunction: a retrospective propensity score analysis - Kattih, Badder; Shirvani, Amir; Klement, Piroska; Martin Garrido, Abel; Gabdoulline, Razif; Liebich, Alessandro; Brandes, Maximilian; Chaturvedi, Anuhar; Seeger, Timon; Thol, Felicitas; Göhring, Gudrun; Schlegelberger, Brigitte; et al. (Leukemia, 2021)
Clonal hematopoiesis of indeterminate potential (CHIP) is linked to leukemia gene mutations and associates with an increased risk for coronary artery disease and poor prognosis in ischemic cardiomyopathy. Two recurrently mutated genes in CHIP and adult acute myeloid leukemia (AML) encode for isocitrate dehydrogenases 1 and 2 (IDH1 and IDH2). Global expression of mutant IDH2 in transgenic mice-induced dilated cardiomyopathy and muscular dystrophy. In this retrospective observational study, we investigated whether mutant IDH1/2 predisposes to cardiovascular disease in AML patients. Among 363 AML patients, IDH1 and IDH2 mutations were detected in 26 (7.2%) and 39 patients (10.7%), respectively. Mutant IDH1 patients exhibited a significantly higher prevalence of coronary artery disease (26.1% vs. 6.4%, p = 0.002). Applying inverse probability-weighting analysis, patients with IDH1/2 mutations had a higher risk for a declining cardiac function during AML treatment compared to IDH1/2 wild type patients [left ventricular ejection fraction pretreatment compared to 10 months after diagnosis: 59.2% to 41.9% (p < 0.001) vs 58.5% to 55.4% (p = 0.27), respectively]. Mechanistically, RNA sequencing and immunostaining in hiPS-derived cardiomyocytes indicated that the oncometabolite R-2HG exacerbated doxorubicin mediated cardiotoxicity. Evaluation of IDH1/2 mutation status may therefore help identifying AML patients at risk for cardiovascular complications during cytotoxic treatment.
Publiziert: 18. September 2020
Gesehen am 23.09.2025